Educating Young Learners to Gender Equality through Movies: Wonder Woman vs Captain Marvel - Endah Wulandari; M. Thoyibi (AL-ISHLAH: Jurnal Pendidikan, 2022)
The issue of fair treatment given to males and females in the classroom discourse is currently discussed worldwide. The notion of gender equality that facilitates similar access for boys and girls to education is among the striving to achieve such conditions. This study tries to give an overview of two popular movies that can be used to disseminate the idea of gender equality to students in elementary schools. Wonder woman and Captain Marvel movies were chosen as the data of this research since the film genre is under the theme of heroism that represents women as the main characters. This research uses Roland Barthes' semiotics approach to analyze the data and John Fiske’s ideology to see the symbols used to describe feminist values that these characters display, supported by communication theory and feminism. The results of the study show that the characters of Captain Marvel and Wonder Woman are depicted as female figures who have greater power than men and show some liberal feminist values. The difference is that Captain Marvel has indirectly different powers from Wonder Woman, who already has powers because she is a demigod. From this finding, it can be inferred that there are some values that are beneficial to introduce to young learners from these movies. However, parental guide when watching is still needed in order to restrict the negative values that are irrelevant with our local culture.